GE_GERICHTE P/12684/2020 vom 23. Juli 2020 - GE Cour de justice (2020)
SOUPÇON;QUALITÉ POUR AGIR ET RECOURIR;COMMUNAUTÉ HÉRÉDITAIRE;REPRÉSENTANT;DROIT DE CARACTÈRE CIVIL | CPP.310; CPP.382; CC.602.al3